UTILIZATION OF ARTIFICIAL AQUIFERS FOR RAINWATER STORAGE (ABSAH) IN GADING KIRANA HOUSING, KELAPA GADING - Mohammad Imamuddin; Tanjung Rahayu; Mira Herliana (University Muhammadiyah Jakarta, 2025)
Jakarta is facing a clean water crisis due to rapid population growth, land subsidence, and fluctuations in the supply of PDAM. This study analyzes the potential application of Artificial Aquifer Storage Rainwater (ABSAH) technology as an alternative solution for providing clean water in densely populated residential areas. The study was conducted in Gading Kirana RW 08 Housing, Kelapa Gading, North Jakarta, with an area of 42 hectares. The research method includes the analysis of BMKG rainfall data at the Tanjung Priok Maritime Meteorological Station for the period 2016–2025, the calculation of the volume of rainwater availability from a roof area of 252.000 m², the analysis of domestic water needs based on SNI 6728.1:2015 (200 liters/person/day), and the planning of the ABSAH system with a depth of 2.5 meters. The results showed that the daily availability of rainwater fluctuated between 2.015,19–9.099,65 m³, while the domestic needs of the community were 1.243 m³/day. The analysis of the water balance shows that there is an annual surplus of 33.159,79 m³ that can be utilized through the ABSAH system. The implementation of the system requires 173 units of ABSAH tubs with a capacity of 150 m³ with dimensions of 12 m × 5 m × 2.5 m, serving a ratio of 7 houses per unit. The ABSAH system integrates rainwater storage, artificial recharge, and flood mitigation functions to support urban water resilience. This study provides a model for the implementation of ABSAH technology for similar residential areas and contributes to the achievement of SDGs related to sustainable clean water access.Keywords: ABSAH, rainwater harvesting, artificial aquifers, urban water resilience, North Jakarta